ПЕДАГОГІЧНІ УМОВИ ПІДВИЩЕННЯ ЯКОСТІ ВОКАЛЬНО-ХОРОВОЇ РОБОТИ В ПРОЦЕСІ НАВЧАННЯ УЧНІВ (Педагогіка вищої та середньої школи, 2010)
It is important for receiving positive results in a vocal-choral work to know and to create pedagogical conditions of rising of the quality of the vocal-choral work in the process of pupils education. Pedagogical conditions of forming of quality of vocal-choral work mean specially created conditions owing to which deep understanding of aesthetic content of a musical composition are carried out and its influence to the personality strengthen.